The Relationship Between Nurse Caring Behavior and Patient Satisfaction Level in Santa Marta and Maria Rooms at Santa Elisabeth Hospital Medan in 2021 - Amelia Sepriani Purba; Mestiana Br. Karo (TOUR HEALTH JOURNAL, 2022)
Caring behavior is a basis in providing professional nursing services. Where a nurse must have empathy, compassion, care, sincerity, and be able to interact well with the patient, the patient's family and everyone. With a caring attitude, the patient who receives the service will feel satisfied because the patient feels that all his needs and expectations have been met. Based on the initial survey, it was found that 10 patients who were interviewed said they were not satisfied, because the nurse's concern in providing services was very low. This study aims to determine the relationship between Nurse Caring Behavior and Patient Satisfaction Levels at Santa Maria and Santa Marta Hospital Santa Elisabeth Medan in 2020. This study used a cross sectional approach. Collecting data using a questionnaire sheet, where the population in this study were patients who were being treated in the Marta and Maria room of the Santa Elisabeth Hospital Medan within the last 2 months and used purposive sampling technique, with a total sample of 64 people. The results showed that 50% caring behavior was very high, 28.1% high, and 21.9% low. Based on the chi square test, the p-value = 0.003 (p <0.05), which means that there is a relationship between Nurse Caring Behavior and Patient Satisfaction in the Santa Marta and Maria rooms at Santa Elisabeth Hospital, Medan. It is hoped that nurses will be able to apply better caring attitudes, show empathy and compassion, so that patients can feel satisfied and to improve the quality of service in the hospital.